SISTEM PAKAR MENDIAGNOSA PENYAKIT IKAN ARWANA (SCLEROPAGES FORMOSUS) UNTUK MEMINIMALISIR PENYEBARAN HAMA DAN PENYAKIT MENGGUNAKAN METODE FORWARD CHAINING: EXPERT SYSTEM, DISEASE, SCLEROPAGES FORMOSUS, FORWARD CHAINING - Astari Prakasiwi, Degita; Wiranata, Ardi (LP2M STMIK Nurdin Hamzah Jambi, 2018)
Unit Pelaksana Teknis Dinas Balai Benih Ikan Daerah (UPTD BBID) Provinsi Jambi is a place for freshwater fish cultivation including arwana. UPTD BBID are diagnosing disease in arwana fish by the help of the employee who are expert in diagnosing the diseases. But this method is difficult and needs time. So, this research aims to build an expert system application to diagnose Arwana fish (scleropages formosus) disease by using forward chaining method. The use of this application expected can minimize the spread of pests and diseases in arwana fish. This application is built using Microsoft Visual Basic Net and MySQL database. The results of consultation tests with this system indicate that the system is able to determine the disease, causes, and prevention and solution based on symptoms previously answered by employees.